Pharmaceutical Equivalence and Similarity Studies of Metoclopramide Tablets - Varillas, María Alejandra (2018)
Dissolution studies have evolved from a simple quality control test to a surrogate of in vivo interchangeability. Pharmaceutical equivalents are drug formulations with the same molar amount of the same active pharmaceutical ingredient (API), in the same dosage form, meet comparable quality standards, and are intended to be administered by the same route. Pharmaceutical equivalents imply therapeutical equivalence when, after administration, their effects are essentially the same; these effects can be demonstrated by bioequivalence studies or, in some cases, by in vitro studies based on the Biopharmaceutics Classification System. In this scheme, biowaivers are recommended for immediate-release solid oral dosage forms containing Class 3 drugs (like Metoclopramide) using dissolution testing as a surrogate for in vivo bioequivalence studies, with special consideration regarding excipient composition. The present work aimed to compare in vitro dissolution characteristics and other critical quality attributes of Metoclopramide tablets purchased in Argentina to establish their pharmaceutical equivalence and similarity. All evaluated products fulfill the pharmaceutical equivalence criteria. Three of the tested products and the reference formulation complied with the criteria for ‘very rapidly dissolving,’ so they could be described as essentially similar. Nevertheless, it is important to have access to additional information about the excipient composition of these formulations to assure a safe interchangeability process for this Class 3 drug.